Artificial Intelligence Application Usage Training: ChatGPT, Gamma, and Bing Image Creator In SMK Taman Siswa Bogor Students - Primasari, Dewi; Kamilah, Nurul; Hermawan, Erwin; Riana, Freza; Laxmi, Gibtha Fitri; Yanuarsyah, Iksal; Hadjimartsu, Sahid Agustian; Eosina, Puspa (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
The development of artificial intelligence technology has opened up new opportunities in the world of education, especially for vocational high school students who need digital skills to compete in the era of the industrial revolution 4.0. However, the implementation of this technology still faces challenges such as low digital literacy and limited infrastructure. This study aims to provide training on artificial intelligence applications (ChatGPT, Gamma, and Bing Image Creator) in improving the digital competence of SMK Taman Siswa Bogor students. The training method uses a participatory approach with three main stages: preparation (needs analysis, material preparation), implementation (theoretical training, direct practice, and case studies), and evaluation (pre-test, post-test, and interview). Participants consisted of 18 students and 2 teachers. Data analysis was carried out quantitatively (statistical tests). The results showed a significant increase in understanding the concept of artificial intelligence (from 32.4% to 78.6%) and mastery of applications (82% for ChatGPT, 79% Gamma, 71% Bing Image Creator). In addition to technical aspects, 88% of participants reported increased motivation to learn and 41% showed interest in technology-based careers. Key challenges included limited infrastructure (23% network issues) and varying participant abilities, which were successfully addressed through differentiated learning approaches and the use of personal devices.